Primary characteristics of the extreme heavy rainfall event over Henan in July 2021 - Jianhua Sun; Shenming Fu; Huijie Wang; Yuanchun Zhang; Yun Chen; Aifang Su; Yaqiang Wang; Huan Tang; Ruoyun Ma (Atmospheric Science Letters, 2023)
Abstract During mid‐July 2021, an extreme heavy rainfall event (HRE) occurred in Henan Province (hereafter “21.7” HRE), with extreme hourly precipitation of 201.9 mm appearing at Zhengzhou station. Our preliminary analyses of the “21.7” HRE using the observations and ECMWF (European Centre for Medium‐Range Weather Forecasts) ERA5 reanalysis data, reached the following conclusions. Favorable configurations of various synoptic weather systems (e.g., strong upper‐level high‐pressure ridge, intense middle‐level low‐pressure trough) acted as crucial background conditions for the occurrence of the “21.7” HRE. A 21‐h long‐lived mesoscale convective vortex (MCV), mainly located in the middle and lower troposphere west of Zhengzhou city, was a key system that produced the extreme hourly rainfall of 201.9 mm·h−1. The MCV's development/sustainment was dominated by the vertical transport of cyclonic vorticity and tilting, as well as the horizontal import of cyclonic vorticity to the vortex's key region. In contrast, the divergence‐related vertical shrinking was the most detrimental factor. Lagrangian moisture transport analysis showed that moisture for the extreme heavy rainfall in Zhengzhou on July 20 mainly came from levels below 2200 m, driven by airflows on the peripheries of tropical cyclones IN‐FA and CEMPAKA. To enhance the understanding of “21.7” HRE, we suggest more in‐depth investigations in the future.